Case Report: A Rare Case of Lupus Nephritis Associated With Mantle Cell Lymphoma - Bao, Daorina; Tan, Ying; Yu, Xiaojuan; Wang, Bingjie; Wang, Hui; Xu, Rong; Zhou, Fude; Zhao, Minghui (Frontiers in Medicine, 2021)
In this research, we described a very rare case of secondary lupus nephritis associated with B-cell lymphoma. An 84-year-old man was hospitalized at our institute for lower extremity edema persisting for over 2 months. He was diagnosed with systemic lupus erythematosus based on clinical and laboratory criteria, which showed impaired renal function and nephrotic syndrome with predominant hematuria. Renal biopsy showed IV+V lupus nephritis with highly infiltrated lymphoid cells in the kidney. Secondary lupus nephritis was suspected based on the possible pathogenesis of glomerular injury due to mantle cell lymphoma. Low-dose dexamethasone, rituximab, and lenalidomide were immediately started on the patient, and his renal function was improved after the first cycle of chemotherapy.